KESIAPAN PETANI TEMBAKAU MENGHADAPI RUU PENGENDALIAN DAMPAK PRODUK TEMBAKAU TERHADAP KESEHATAN DI KABUPATEN TEMANGGUNG - Alfina Handayani; Nurdjanah Nurdjanah; Lili Kresnowati; Eny Hari Widowati (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2012)
Tabacco industry has important role for Indonesia income and absorp a lot of labor force. However, based on some researchs, tobacco product such cigarettes tend to cause many dangerous desease. On the other hand, many restriction efforts to limit negative effect of tobacco have much protest especially in Kabupaten Temanggung. The aim of the research is to analize farmer readiness based on their knowledge and attitude to draft the law of controlling of tabacco product effect to health. The research is conducted at Kabupaten Temanggung by select district that most produce tobacco. The number of sample is 210 respondents used rapid survey method and Csurvey system. Quantitative data is analyzed as descriptif with frequency distribu tion tables. Qualitative data is analyzed by data categorization, matriks, and summary from each respondent, contextualitation and naratif analisys. The result showed that generally tobacco farmer is not ready to draft the law of controlling of tabacco product effect to health yet. The farmer unreadiness bases on their wrong knowledge with the content of draft the law and their negative attitude